Identifying the components of a project-based curriculum model with an emphasis on a task-based approach in technical and vocational education - Hadilou, Nasrin; Baghaei, Hossein (Assessment and Practice in Educational Sciences, 2026)
Introduction and Objective: The Technical and Vocational Education Organization is the most important skill and applied center in the country and is related to the International Labor Organization. It has a special position due to its legal mission in providing the field of education and mastering general training and spreading the culture of work and entrepreneurship. In the present study, an attempt has been made to identify the components of the project-based curriculum model in technical and vocational education.Method: This study was conducted as a systematic review with the aim of identifying and analyzing the components of the higher education curriculum. The statistical population included scientific articles published between 2015 and 2024 in the fields of curriculum planning, modern teaching methods, and learning theories. A search was conducted in reputable international and Persian databases using combined keywords. The articles were screened in three stages based on specific inclusion and exclusion criteria, and quality assessment was performed using the PRISMA checklist. The data were reviewed using descriptive qualitative content analysis and the findings were extracted in the form of themes.Results: The findings showed that a project-based learning curriculum with a task-based approach in technical and vocational education includes three key dimensions. The first dimension is project-based learning, which strengthens critical thinking skills and creativity by emphasizing experience, problem solving, and the production of a general product. The second dimension is task-based learning, which establishes the connection between theoretical knowledge and applied skills through preparation, task execution, and post-action reflection. The third dimension is dedicated to curriculum development and emphasizes industry participation, the integration of technical and soft skills, and flexible learning paths. Conclusion: Overall, the results of the study indicate that the combination of project-based and task-based approaches can provide a comprehensive model for designing modern curricula in technical and vocational education that, in addition to promoting specialized knowledge and skills, also has the ability to respond to the changing needs of industry and society.